Dataset for the Reporting of Gestational Trophoblastic Neoplasia: Recommendations From the International Collaboration on Cancer Reporting (ICCR). (24th November 2022) - Hui, Pei; Webster, Fleur; Baergen, Rebecca N.; Buza, Natalia; Cheung, Annie N.Y.; Kaur, Baljeet; Ronnett, Brigitte M.; Shih, Ie-Ming; Seckl, Michael J.; Lax, Sigurd F.; McCluggage, W. Glenn
Abstract : Comprehensive pathology reporting of cancers is important for patient management, tumor staging, and prognostication. Standardized cancer datasets are essential in guiding pathology reporting in a consistent and concise manner and this facilitates effective global cancer information exchange and comparison. The International Collaboration on Cancer Reporting (ICCR) is an alliance of several national and international pathology societies in many countries as well as bodies which are involved in tumor classification and staging. One function of the ICCR is to develop evidence-based, standardized reporting datasets for each cancer site. Herein, we report the development of an evidence-based cancer dataset by an ICCR panel of international experts for the reporting of primary uterine gestational trophoblastic neoplasia. We present the core elements that should be included and noncore elements that are recommended for inclusion in pathology reports. Lists of the response values are provided for each element, along with explanatory commentaries. The dataset also discusses controversial issues in the reporting of gestational trophoblastic neoplasia. Such evidence-based and structured pathology datasets developed through an international effort will facilitate consistent and accurate exchange and comparison of epidemiological and pathologic parameters among different populations and countries. This will ultimately improve gestational trophoblastic neoplasia patient care and facilitate future research.